Sevoflurane‐induced isoelectric EEG and burst suppression: differential and antagonistic effect of added nitrous oxide. (8th March 2017) - Niu, B.; Xiao, J. Y.; Fang, Y.; Zhou, B. Y.; Li, J.; Cao, F.; Tian, Y. K.; Mei, W.
Summary: The objective of this study was to investigate whether nitrous oxide influenced the ED50 of sevoflurane for induction of isoelectric electroencephalogram (ED50isoelectric ) differently from its influence on the ED50 of sevoflurane for electroencephalogram burst suppression (ED50burst ). In a prospective, randomised, double‐blind, parallel group, up–down sequential allocation study, 77 ASA physical status 1 and 2 patients received sevoflurane induction and, after tracheal intubation, were randomly allocated to receive sevoflurane with either 40% oxygen in air (control group) or 60% nitrous oxide in oxygen mixture (nitrous group). The ED50isoelectric in the two groups was determined using Dixon's up and down method, starting at 2.5% with 0.2% step size of end‐tidal sevoflurane. The electroencephalogram was considered as isoelectric when a burst suppression ratio of 100% lasted > 1 min. The subsequent concentrations of sevoflurane administered were determined by the presence or absence of isoelectric electroencephalogram in the previous patient in the same group. The ED50isoelectric in the nitrous group 4.08 (95%CI, 3.95–4.38)% was significantly higher than that in the control group 3.68 (95%CI, 3.50–3.78)% (p < 0.0001). The values for ED50burst were 3.05 (95%CI, 2.66–3.90)% and 3.02 (95%CI, 3.00–3.05)% in nitrous group and control group, respectively (p = 0.52). The addition of 60% nitrous oxide increases ED50isoelectric, but not the ED50burst of sevoflurane. Neither result indicates an additive effect of anaesthetic agents, as might be expected, and possible reasons for this are discussed.